An introductory guide to cloud load balancing techniques - Mingyue Wang (Big Data and Computing Visions)
The goal of research in the intriguing area of cloud computing is to discover the most effective solution and method for sharing and protecting data. Load Balancing (LB) on public infrastructure using cloud computing's ideal geographic location. In cloudy environments, LB is widely used as a visitor control approach. Cloud requests look for resources to support performance. The resources are frequently things like bandwidth, processing power, and storage. LB is the process of effectively allocating these resources to each competing job. This study will offer a thorough analysis of cloud load-balancing methods.